INTRODUCTION: THE POWER OF NUCLEAR THINGS - Hecht, Gabrielle (Being Nuclear, 2012)
In late 2002, US President George W. Bush announced that Iraqi dictator Saddam Hussein had “recently sought significant quantities of uranium from Africa.” The implication? Iraq planned to build nuclear weapons, and the world must act. The scenario seemed plausible. Weapons inspectors had uncovered a clandestine program after the 1991 Persian Gulf War. Surely Saddam would try again. Bush and his advisors had been implying this for months, releasing assorted evidence to make the case. US national security advisor Condoleezza Rice insisted, for example, that Iraq had imported aluminum tubes whose only conceivable use was in a nuclear weapons program.